Energy transfer process and evolution characteristics in impeller of contra-rotating axial fan - Yongping CHEN; Ronghua LIU; Shiqiang CHEN; Dong LIU; Yangyi LI; Xiao WANG (Meitan kexue jishu)
Energy is transferred to the airflow during the rotation of impeller. In engineering, the efficient energy conversion is a key issue. Mastering the energy transfer process in impeller is the premise and basis for realizing efficient energy conversion. In order to clarify the energy transfer mechanism in impeller of contra-rotating axial fan, the internal flow field in impeller was obtained by numerical simulation and experiment. Based on the turbomachine energy conversion theory, the evolution characteristics of parameters such as flow angle, axial velocity and local theory total pressure rise were analyzed, and the laws of energy distribution and flow loss process in impeller were clarified. The results show that the efficiency of front impeller is significantly higher than that of the rear impeller when the flow rate is greater than 0.7 QBEP (QBEP is flow rate at the best efficiency point). When Q=1.0 QBEP, the efficiency difference between the two-stage impellers is about 26.5%, and the efficiency difference is as high as 66.6% when the flowrate increases to 1.22 QBEP, which indicate that the low efficiency of the rear impeller is the main reason for the efficiency reduction of the fan. In the streamwise location, the flow loss of the rear impeller is concentrated within STL=0−0.3 (STL represents the dimensionless distance from the inlet to outlet of the impeller in the flow direction), and reducing the flow loss in this region is the key to improve the efficiency of rear impeller. The hump characteristic of actual total pressure rise curve is the result of the combined effect of theory total pressure rise and flow loss, but mainly related to the theory total pressure rise at the outlet of front impeller and inlet of rear impeller. The sharp decrease or increase in flow angle at the spanwise direction is the main cause of a significant decrease in axial velocity, which in turn leads to backflow in the inlet and outlet of the front impeller and inlet of the rear impeller within SPN=0.8−1.0 (SPN represents the dimensionless distance from the hub to shroud of the impeller in the spanwise direction), and ultimately affects the theory total pressure rise in impeller. Therefore, the flow angle and axial velocity jointly affect the energy evolution law in impeller. The local theory total pressure rise is greatly improved in the middle region of the impeller, while the change in the inlet and outlet region is negligible. The significant increase growth rate of local theory total pressure rise is the key factor determining the theory total pressure rise of the impeller.